(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2024)
Identification and recognition of gender-dis aggregated constraints, gender imbalances, differentials in gender roles, and decision-making on agriculture production, technology transfer, and input utilization are essential to the transformation of research output to benefit women and men. This study aimed to assess gender integration in selected agricultural practices and gender division of labor in the Gedeo and Halaba Zones. The study employed a cross-sectional design. The sample respondents were randomly 86 men and 69 women farmers, and a total of 155 farmers were selected to collect the data through triangulation of key informants interviews, focus group discussion, and household survey. The data was analyzed using descriptive statistics. Data analysis results in the frequency of men and women’s participation computed. Different gender participation factors evaluated. According to the data analysis result, the effect of community norms was assessed among 155 respondents, men 54 (34.8%), 0 (0%), and 15 (9.7%), responded as yes, no and undecided, respectively. Similarly, women participants believed that 64 (41.9%), 1 (0.6%), and 36 (23.2%), responded as yes, no and undecided, respectively. Decision-making could affect gender participation. Men 66 (42.6%), 1 (0.6%) and 20 (12.9%) responded as yes, no and undecided, respectively. Likewise, women participants believed that 53 (34.2%), 1 (0.6%) and 15 (9.7%), responded as yes, no, and undecided, respectively. Concerning care workmen 65 (41.9%), 0 (0%) and 21 (135%), responded as yes, no and undecided, respectively. Similarly, women participants believed that 54 (34.8%), 0 (0%) and 15 (9.7%), responded yes, no and undecided, respectively. Average task share of the household is 30%, 15%, 43% and 12% for men, boys, women and girls, respectively. Women and men performed a larger share of the gender role in rural households than boys and girls. The reproductive work of women in the household covered 67% of the total household care work. The gender participation index in selected agricultural practices was 0.709. However, the Participation Index of men was found to be 0.55 and that of women was 0.45. According to this statistical result, household members spent agricultural labor hours differently, as converting this labor share into daily labor hours indicated that women, men, boys, and girls are spending 10, 7, 4 and 3 hours per day on average, respectively. Int. J. Agril. Res. Innov. Tech. 14(1): 1-9, June 2024